2022
DOI: 10.3390/jrfm15120563
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Audit Committee Chair Characteristics on Financial Reporting Quality

Abstract: This study examines the extent to which the characteristics of the audit committee chair enhance the quality of financial reports and reduce the possibility for companies to receive a modified audit opinion (MAO) from an external auditor. We apply logistic regression to investigate the influence of Audit Committee Chair (ACC) characteristics on the FRQ (FRQ), for a sample of 460 firm-year observations (service and industrial company listed) on the Amman stock exchange for the years 2017–2020. This study uses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The partial least squares (PLS) analysis with Smart PLS was used in this study to test the formulated hypotheses and to analyze the research model. PLS describes as capable of examining various relationships simultaneously and it is appropriate to examine complex models having multiple items, variables and relationships (Lutfi et al, 2021;Lutfi et al, 2022d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The partial least squares (PLS) analysis with Smart PLS was used in this study to test the formulated hypotheses and to analyze the research model. PLS describes as capable of examining various relationships simultaneously and it is appropriate to examine complex models having multiple items, variables and relationships (Lutfi et al, 2021;Lutfi et al, 2022d).…”
Section: Discussionmentioning
confidence: 99%
“…The partial least squares (PLS) analysis with Smart PLS was used in this study to test the formulated hypotheses and to analyze the research model. PLS describes as capable of examining various relationships simultaneously and it is appropriate to examine complex models having multiple items, variables and relationships (Lutfi et al , 2021; Lutfi et al , 2022d). It is also capable of treating small-sized samples (Lutfi et al , 2022a), indicating that normal distribution is not one of its prerequisites (Hair et al , 2019), which makes it useful for cases that cannot be analyzed using other methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of IS, studies presented system use as the effort level in using the system, equating to the system's output degree in light of a time unit ( Almaiah et al, 2022a ; Trice & Treacy, 1988 ). Using IS is primarily dependent on its assessment by the user and if the user believes that task performance is enhanced through such use, satisfaction and frequency of use will eventually follow suit ( Almaiah et al, 2022b ; Bokhari, 2005 ; Lutfi et al, 2022f ). User satisfaction refers to the user's degree of perception of information that the system provides meeting of his/her needs, and thus, it relates to the experience of the user in using the system, his satisfaction and the result of his use of the information in his reaching decisions ( Al-Khasawneh & Lutfi, 2013 ; Almaiah et al, 2022c ; Chou et al, 2014 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…On the other hand, effective audit committee characteristics are crucial for helping the company make long-term sustainable progress (Asaolu et al, 2022). Several studies have confirmed the value of the AC in improving firm performance, reducing accounting flaws in internal controls and improving financial reporting quality (Lutfi et al, 2022;Kusnadi et al, 2016;Lisic et al, 2016). ACs serve a crucial role in guaranteeing the integrity of financial reporting, and thus, the committee's characteristics and membership have a substantial impact on the financial performance of corporate organizations (Weber, 2020;Kang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%